2023
DOI: 10.1098/rstb.2022.0058
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis decreases with increasing antibiotic pressure but not temperature

Abstract: Predicting mutational effects is essential for the control of antibiotic resistance (ABR). Predictions are difficult when there are strong genotype-by-environment (G × E), gene-by-gene (G × G or epistatic) or gene-by-gene-by-environment (G × G × E) interactions. We quantified G × G × E effects in Escherichia coli across environmental gradients. We created intergenic fitness landscapes using gene knock-outs and single-nucleotide ABR mutations previously identified to vary in the extent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Besides the inherent challenges of predicting phenotypes posed by sign epistasis, the potential influence of the environment adds further complexity. It has been demonstrated that the occurrence or magnitude of sign epistasis can be altered by the environment, including the presence of inducers or inhibitors ( Baier et al, 2023 ) and antibiotics ( Ghenu et al, 2023 ). Nevertheless, the impact of other environmental factors on sign epistasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the inherent challenges of predicting phenotypes posed by sign epistasis, the potential influence of the environment adds further complexity. It has been demonstrated that the occurrence or magnitude of sign epistasis can be altered by the environment, including the presence of inducers or inhibitors ( Baier et al, 2023 ) and antibiotics ( Ghenu et al, 2023 ). Nevertheless, the impact of other environmental factors on sign epistasis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the adaptation of bacteria to high concentrations of antibiotics in their habitat will be favored in bacterial strains with genetic elements such as plasmids and integrons that allow them to survive in these conditions. A recent study where it was predicted how gene-by-gene by-environment (G × G × E) interactions affect the evolution of E. coli against pressure at various concentrations of antibiotics, it was shown that G × G interactions and rugged fitness landscapes in the absence of antibiotics, but as antibiotic concentration increased, the fitness effects of ABR genotypes quickly overshadowed those of gene knock-outs, and the landscapes became smoother [ 31 ], suggesting that the evolution of resistant bacteria to antibiotics is facilitated by extreme habitats (with the presence of antibiotics) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the h4 loss of D mutation altered MCg1 function, it seems plausible that it was compensated by an array of stabilizing mutations at various sites in the protein, fostering MCg1-specific divergence from its ancestral state [44]. Though epistatic drift through intramolecular interactions may render protein evolution less predictable [45], stressful and/or adverse environments exerting strong selective pressure can channel such a process [46]. This seems to be the case with the expansive divergence of the (D4XFA5) Bordetella-Achromobacter MCg1 clade wherein structural divergence suggests shifted constraints that could stabilize MCg1 functional evolution in these emerging bacterial spp.…”
Section: Discussionmentioning
confidence: 99%